Pelatihan Software Desain dan Artificial Intelligent (AI) untuk Siswa Sekolah Menengah Kejuruan (SMK) - Hasanudin; Ardi Nugroho Yulianto; Ahmad Nasirudin; Wasis Dwi Aryawan; Hesty Anita Kurniawati; Erzad Iskandar Putra; Danang Waspandri; Alvian Syiham Risal; Nixon Faldias Salman; Nisrina Az Zahra; Muhammad Abid Athoillah; Muhammad Rozzaqi Husein; Khisan Sabilarahma; Muhammad Fakhrudin; Andrianto Bayu Pamungkas; Ovanie Rizkiana Ali Efendi; Ahmad Hamdiy Ar Raa Biiy; Andi Muhammad Almusadieq; Muhammad Reza Yudha Pratama; Muhammad Rafli; Reynard Lisan (Sewagati, 2026)
This training aims to provide vocational high school (SMK) students majoring in shipbuilding with practical knowledge and skills in using design software and applying Artificial Intelligence (AI) technology in the ship design process. The program introduces software for building 2D and 3D ship models and demonstrates how AI enhances design efficiency and accuracy. The training is centered at SMK Negeri 2 Surabaya. The location was changed from ITS due to the approaching End-of-Semester Exams (UAS) for schools throughout Surabaya, which would complicate student mobilization to the campus. By centralizing the location at the SMK, the participants' learning focus can be optimized. Each school sends participants to attend the material and practice sessions, which are supervised by competent teachers. In addition to classroom sessions, students are introduced to the ITS campus environment and the shipbuilding industry process through video screenings. This includes virtual tour videos of laboratories (Ship Design, Digital, Construction, and Production) and a documentary video about the National Ship Design and Engineering Center (NaSDEC) as the culminating activity. This training is expected to equip students with new skills to support human resource development in the shipbuilding sector.